Edisi Teks Naskah Shiyam Ramadhan - Restati Yelni; Miftahul Ilmi; Tuti Harianty (Jurusan Bahasa dan Sastra Arab Fakultas Adab dan Humaniora UIN Imam Bonjol Padang, 2019)
This study carried out an edition of the text on the ShiyamRamadhan manuscript found in one of the scriptorium in the form of aresident's house in Kerinci Regency. The researcher conducted a textedition with diplomatic and standard edition techniques. Both editionsare presented according to the methods and work steps that have beendetermined. The results of the text edition with diplomatic methodsand standards are then described using content analysis. The authorfound the existence of locality values in the text when describing thetopic of fasting in Ramadhan. The results of the text edition andreview of the contents lead the writer to the conclusion that culturalacculturation in the spread of Islamic syari'ah was found in Kerincidistrict.